2017
DOI: 10.1542/peds.2016-3000
|View full text |Cite
|
Sign up to set email alerts
|

Early Probiotic Supplementation for Eczema and Asthma Prevention: A Randomized Controlled Trial

Abstract: For high-risk infants, early LGG supplementation for the first 6 months of life does not appear to prevent the development of eczema or asthma at 2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 28 publications
4
88
1
3
Order By: Relevance
“…Coming enthusiastically from these animal studies into the human system, the application of probiotics to high-risk children in the first 6 months of life did not show any significant differences for asthma incidence at the age of 5 years, although a trend was found with 17.4% affected by asthma in the control group vs. 9.7% in the LGG-treated children [149].…”
Section: Asthma Prevention I) Probioticsmentioning
confidence: 95%
“…Coming enthusiastically from these animal studies into the human system, the application of probiotics to high-risk children in the first 6 months of life did not show any significant differences for asthma incidence at the age of 5 years, although a trend was found with 17.4% affected by asthma in the control group vs. 9.7% in the LGG-treated children [149].…”
Section: Asthma Prevention I) Probioticsmentioning
confidence: 95%
“…A study, however, showed that continuous administration of 10 7 colony‐forming units Lactobacillus gasseri for 4 weeks prevented Dermatophagoides pteronyssinus (house dust mites) induced inflammation of airway in mouse models of allergic asthma . However, a randomized trial on humans showed that Lactobacillus supplementation for the first 6 months does not seem to cause a decreased rate of development of asthma . In terms of increased abundance of Bacteriodaceae , a separate study showed that children that develop asthma show low diversity of gut microbiota with predominance of Bacteriodaceae .…”
Section: Dysbiosis and The Development Of Asthma In Children Born To mentioning
confidence: 99%
“…44 However, a randomized trial on humans showed that Lactobacillus supplementation for the first 6 months does not seem to cause a decreased rate of development of asthma. 45 In terms of increased abundance of Bacteriodaceae, a separate study showed that children that develop asthma show low diversity of gut microbiota with predominance of Bacteriodaceae. 46 This shows that an asthmatic mother can increase the chance of the child of developing asthma in a non-genetic mechanism via increasing abundance of Bacteriodaceae and decreasing that of Lactobacillus.…”
Section: Development Of Asthma In Children Born To Asthmatic Mothersmentioning
confidence: 99%
“…Thus, L. plantarum IS-10506 was able to reduce clinical symptoms in children diagnosed with AD and therefore with potential to treat this disease (Prakoeswa et al 2017). Cabana et al (2017) evaluated the effectiveness of daily L. rhamnosus GG supplementation for the first 6 months of life to decrease eczema incidence, a potential early marker of asthma. The intervention infants received a daily dose of L. rhamnosus GG (1 × 10 9 CFU) and inulin (225 mg), and the control infants received inulin (325 mg) alone.…”
Section: Oral Administration Of Probiotics and Prebiotics For The Trementioning
confidence: 99%